2019
DOI: 10.1007/s10902-019-00089-8
|View full text |Cite
|
Sign up to set email alerts
|

Materialism and Well-Being Revisited: The Impact of Personality

Abstract: Although the negative link between materialism and well-being has been confirmed by results from many empirical studies, mechanisms underlying this association still remain partially unexplained. The issue is addressed in this article in two ways. Firstly, the nature of the components of materialism is examined, and secondly-the article demonstrates that personality (particularly neuroticism and narcissism) is one of the important factors linking materialism and well-being. The article presents the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…Therefore, the following hypotheses are proposed. Hypothesis 1: The “peacock” and “mouse” type materialists will be replicated in a North American sample. The two types were found in both Studies 1 and 2 in the research by Gornik-Durose and Pilch (2016), and additional evidence for the dual-nature model has been provided by Gornik-Durose (2020); however, this finding has not been replicated in a sample in a different culture from the original. Hypothesis 2a: Materialism is correlated with future-negative TP. This is likely as materialism and future-negative TP are both positively related to neuroticism and negatively related to well-being (Dittmar et al., 2014; Stolarski & Matthews, 2016).…”
Section: Future-negative Tpmentioning
confidence: 86%
“…Therefore, the following hypotheses are proposed. Hypothesis 1: The “peacock” and “mouse” type materialists will be replicated in a North American sample. The two types were found in both Studies 1 and 2 in the research by Gornik-Durose and Pilch (2016), and additional evidence for the dual-nature model has been provided by Gornik-Durose (2020); however, this finding has not been replicated in a sample in a different culture from the original. Hypothesis 2a: Materialism is correlated with future-negative TP. This is likely as materialism and future-negative TP are both positively related to neuroticism and negatively related to well-being (Dittmar et al., 2014; Stolarski & Matthews, 2016).…”
Section: Future-negative Tpmentioning
confidence: 86%
“…Second, we can regard egocentrism as a defense mechanism to cope with the negative experience of self-inadequacy by self-inflation (i.e., Freudian defense mechanism of “reaction formation”). Third, there are some studies showing a positive relationship between materialism and narcissism [ 21 , 22 ] and a negative relationship between materialism and empathy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Greene et al [ 25 ] showed that sensation seeking and egocentrism predicted risk-taking behaviors in adolescents. Górnik-Durose [ 21 ] showed that narcissism (a concept closely related to egocentrism) served as a mediator between materialism and well-being indicated by emotional well-being and psychological well-being. In conjunction with the above-mentioned findings on the relationship between materialism and egocentrism, we proposed that egocentrism may serve as a mediator of the influence of materialism on adolescent delinquency.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that self-transcendence is negatively related to depression ( Reed, 1991 ; Ellermann and Reed, 2001 ; Haugan and Innstrand, 2012 ) as well as neuroticism ( Levenson et al, 2005 ). In contrast, materialism has been positively associated with depression ( Kasser and Ryan, 1993 ; Dittmar et al, 2014 ) as well as neuroticism ( Sharpe and Ramanaiah, 1999 ; Burroughs and Rindfleisch, 2002 ; Watson, 2015 ; Górnik-Durose, 2019 ).…”
Section: Hypotheses and Analytical Planmentioning
confidence: 91%